Abtractization of incidental constitutional control, the effectiveness of decisions and the constitutional mutation of article 52, X of Brazil’s Constitution: a response for criticism - Valério, Guilherme Lucas (2020)
The work finds an answer for the criticism about the constitutional mutation of article 52, X in Brazil’s Constitution position thought by part of the doctrine and endorsed by the Supreme Court in your current composition. The comprehension proposes made a system from the decisions of the Court to be respected from objective or incidental control. In spite of that, one cannot forget about some existing institutes in the national law, reason why they cannot be dematerialized. For the purpose, introduces the definitions and more important concepts for the main theme followed about constitutional control and constitutional mutation, followed by the performance of each power in constitutional control and the exposed of all criticism that reduces the importance of this meaning. By the consequence of this, the article pretends a harmonic understanding of the mutation and the current constitutional control system by an appreciation of precedent as an evolutional jurisprudential tool.